Factor of active participation engineering and technical student-athletes in co-curricular activities (Sport) - Rozali, Mohd Zulfadli; Puteh, Saifullizam; Ismail, Affero; Marian, Mohd Fairuz; Mohamed, Firdaus (Kolej Komuniti Sungai Siput, 2020)
Active participation among engineering and technical student- athletes in co-curricular activities is viewed from different side which is some of them were represent national, universities, faculties in sporting event. Therefore, the purpose of this research was to examine the factors that encourage active participation student participation in co-curricular activities (sports) among engineering and technical students of University Tun Hussein Onn Malaysia (UTHM) who are participate actively in co-curricular activities (sports). Identifying the factors and perception of active participation engineering and technical student- athletes in co-curricular activities (sports) are the main focus on this study. Quantitative research design by using survey were approach on this study. Survey were conducted into two hundred and thirteen student of engineering and technical student-athletes UTHM who are participate actively in co-curricular activities (sports). Findings shows student- athletes agreed that interpersonal, intrapersonal and structural factors are the reason why they involve in co-curricular (sports) activities. These findings could help the university to create active participation environment among engineering and technical student- athletes in co-curricular activities (sports) and at the same time help on producing student-athletes who are able represent university and also national at international levels.